The Influence of Academic Supervision Activities, School Culture, Infrastructure, on the Quality of Learning Processes and Outcomes at Madrasah Aliyah - Ihsan Mustofa; Sutaryat Trisnamansyah; Agus Mulyanto; Husen Saeful Insan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The lack of optimal quality of education in madrasahs causes the public image of madrasas to remain poor. The public view of Madrasahs is associated with second-choice educational institutions, not developed, slums, and other negative images about madrasas, therefore, the desire of the community (parents) to continue their children's studies in madrasahs is very lacking. For the quality of learning in madrasah to increase, the head of the madrasah must always improve the effectiveness of the implementation of academic supervision, improve good school culture, and prepare educational facilities. The results of the pre-survey on the quality of learning at Madrasah Aliyah in South Lampung District, the initial data obtained on the quality of the learning process are as follows: (1) there are still many teachers using less varied learning methods; (2) teachers rarely make use of and use instructional media; (3) learning activities do not activate students, where teachers are more active in learning; (4) the evaluation activities carried out by the teacher were more on the cognitive aspects; (5) learning activities carried out by the teacher do not optimize the development of all potential students; and (6) student learning outcomes are rarely followed up, the information is merely to find out the extent of the learning outcomes of students (students).